HUBUNGAN KONTRASEPSI HORMONAL DAN PARITAS DENGAN USIA MENOPAUSE DI DESA BATANG KUMU TAHUN 2023 - Nana Aldriana,; Edelweiys, Intan R.E (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Women's health problems, one of the reproductive systems, are now becoming world attention is not only related to pregnancy and childbirth but more broadly that is menarche until to menopause. Menopause mark end period reproduction of a woman and usually occurs in women between the ages of 45-54 year. This is due to the reproduction factor, the wrong number of parity and history usage KB Hormonal. Study This aim For know connection Parity(amount child) And Use Contraception Hormonal to Age Menopause. As for population in study women in menopause age as much 50 person with use total sampling . Data in this research is primary data, researchers conduct direct research on menopausal mother. The data analysis used is univariate and bivariate. From the results In this study, there is a relationship between contraceptive use and meopausal age p-value of 0.033 <0.05, Parity has a relationship with menopausal age with p-value 0.046. Keywords : Parity, Hormonal Contraception, Age of Menopause